Digital Vigilantism and the Crisis of Formal Legal Legitimacy: A Socio-Legal Analysis of the Influence of Social Media on Law Enforcement in Indonesia - Rani Lestari; Renni Aryani; Aulia Azhari; Angga Dimas Pratama (Faculty of Law, University of Dr. Soetomo, 2026)
The rise of social media has given rise to the phenomenon of digital vigilantism—a form of social punishment through naming, shaming, and online campaigns that occurs before formal judicial proceedings are concluded. This phenomenon not only reflects an expression of collective anger but also indicates a transformation in the relationship between society and the formal legal system. This study aims to analyze digital vigilantism as a response to the crisis of legal legitimacy and its implications for the independence of law enforcement and the rule of law through a normative legal method using a qualitative approach based on literature review and case analysis in Indonesia. Research findings indicate that digital vigilantism is a form of public participation influenced by shifts in social structure and legal awareness, with social media serving as a new arena for the establishment of legal legitimacy that can expedite official responses, enhance transparency, and create opportunities for victim advocacy; however, it also gives rise to ambivalence due to its potential to foster selective justice based on virality, legal populism, and the erosion of the presumption of innocence through trial by social media. Philosophically, this phenomenon risks fueling moral panic, the tyranny of the majority, cancel culture, and digital authoritarianism—trends that shift the legitimacy of the law from procedural rationality toward collective emotion. Therefore, a balance is needed between digital public participation and the protection of due process of law through enhanced government responsiveness and transparency, as well as the strengthening of the public’s legal literacy and digital ethics, to support substantive justice within Indonesia’s legal system.